Aflatoxin in Animal Feed in Indonesia: The Regulation on The Toxic Content and The Development of Detection Technique - Sri Rachmawati (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2005)
Aflatoxin contamination of agricultural commodities including feedstuff potentially occurs in Indonesia, and can cause problem to animal health and productivity . To minimize the impact of such contamination to both human and animal health, regulations regarding feed quality have been issued by the government . A continuous monitoring of the contamination using a simple, sensitive, rapid and cost-effective method is greatly needed. This paper contains some information about the current situation of aflatoxin contamination in feed and its ingredient (corn), the regulation related to aflatoxin contamination and the development of detection technique for analysis aflatoxin B, in feedstuffconducted by Research Institute for Veterinary Science (RIVS). From research results, inter laboratory studies and collaboration research conducted in Indonesia, they indicate that poultry feed collected from different areas of Indonesia is contaminated by aflatoxins . Results of inter laboratory study and collaborative research with Feed Lab, Directorate General for Livestock Services (DGLS) showed that 14 .0% of 207 feed samples from different sources contain aflatoxin above the standard determined by Standar Nasional Indonesia (SNI) . Regulations related to aflatoxin content in feed are compiled in the SNI (revised formed), the Minimum Technical Requirement of feed concentrate for ruminant and non ruminant, and the regulation from DGLS, letter No 524/TN .250/Kpts/DJP/Deptan/1997. RIVS developed an ELISA technique for analysis aflatoxin in feed and corn, which was involving some steps of activities include hapten synthesis, production and characterization of antibody, development of assay performance, designing a method as a prototype kit . For validation of this technique, RIVS has conducted a training workshop and a field trial . Rapid assay ELISA kit has been designed with incubation time of 5 minutes for conjugate and 10 minutes for substrate . Antibody response was specific to AFB, (100%) with cross reactivity of 0 .9, 3 .5 and 1 .6% for aflatoxins B,, G, and G,, respectively . The limit of detection of AFB, was 0 .3 ppb . The range of analysis is from 0 .3 ppb up to 30 ppb . An ELISA kit composed of seven bottles of AFB, standards solution of 30 . 10, 3 .3, 1 .2, 0 .4, and 0 .12 ppb and blank (0 ppb AFB,), a conjugate of AFB I-HRPO, a substrate, a stopping solution, an antibody coated plate, and one mixing plate . The kit was stable at 4 °C for two months . The field trial of ELISA kit showed an accurate result and when comparing the ELISA method with the standard method of HPLC, a consistent result was also found . With the information given above, people or farmers should be aware of the danger of aflatoxin and should take precaution to prevent aflatoxin contamination . RIVS ELISA kit is a useful technique to detect aflatoxin in feedstuff and, hence, controlling the aflatoxin contamination . Keywords: Aflatoxins, ELISA, detection, feed